This is where it ends - Nijkamp, Marieke (Naperville, Illinois : Sourcebooks Fire, 2016)
Minutes after the principal of Opportunity High School in Alabama finishes her speech welcoming the student body to a new semester, they discover that the auditorium doors will not open and someone starts shooting as four teens, each with a personal reason to fear the shooter, tell the tale from separate perspectives.
Keywords: School shootings -- Fiction; High schools -- Fiction; Schools -- Fiction; Interpersonal relations -- Fiction